Relasi Religiusitas dan Perhatiannya Orangtua dengan Moral Peserta Didik di Kelas X SMK Yosonegoro - Wawan Sunoto (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Morality is an important element in forming a student's character. Therefore, research with the theme of religiosity, parental attention, and morality is important to implement. This research includes the quantitative category. Objects of this research is students in the ten class and the data collection method uses online his survey. The analysis is with product moment correlation analysis technique, which has previously tested its validity, reliability, normality, linearity and hypothesis. In this research to find out [1] the relationship between religiosity to morality, and [2] the relationship between parents' attention to students' morality. The results show that prove it: [1] A fairly strong relationship between religiosity and student morality, with a correlation coefficient of 0.571. [2] Strong relationship between parents' attention to students’ morals, with a correlation coefficient of 0.614.